Mechanical Thrombectomy for Minor and Mild Stroke Patients Harboring Large Vessel Occlusion in the Anterior Circulation: A Multicenter Cohort Study. Issue 12 (December 2017) - Dargazanli, Cyril; Arquizan, Caroline; Gory, Benjamin; Consoli, Arturo; Labreuche, Julien; Redjem, Hocine; Eker, Omer; Decroix, Jean-Pierre; Corlobé, Astrid; Mourand, Isabelle; Gaillard, Nicolas; Ayrignac, Xavier; et al.
Abstract : Background and Purpose—: Proximal large vessel occlusion (LVO) is present in up to 30% of minor strokes. The effectiveness of mechanical thrombectomy (MT) in the subgroup of minor stroke with LVO in the anterior circulation is still open to debate. Data about MT in this subgroup of patients are sparse, and their optimal management has not yet been defined. The purpose of this multicenter cohort study was to evaluate the effectiveness of MT in patients experiencing acute ischemic stroke (AIS) because of LVO in the anterior circulation, presenting with minor-to-mild stroke symptoms (National Institutes of Health Stroke Scale score of <8). Methods—: Multicenter cohort study involving 4 comprehensive stroke centers having 2 therapeutic approaches (urgent thrombectomy associated with best medical treatment [BMT] versus BMT first and MT if worsening occurs) about management of patients with minor and mild acute ischemic stroke harboring LVO in the anterior circulation. An intention-to-treat analysis was conducted. The primary end point was the rate of excellent outcome defined as the achievement of a modified Rankin Scale score of 0 to 1 at 3 months. Results—: Three hundred one patients were included, 170 with urgent MT associated with BMT, and 131 with BMT alone as first-line treatment. Patients treated with MT were younger, more often received intravenous thrombolysis, and had shorter time to imaging. Twenty-four patients (18.0%) in the medical group had rescue MT because of neurological worsening. Overall, excellent outcome was achieved in 64.5% of patients, with no difference between the 2 groups. Stratified analysis according to key subgroups did not find heterogeneity in the treatment effect size. Conclusions—: Minor-to-mild stroke patients with LVO achieved excellent and favorable functional outcomes at 3 months in similar proportions between urgent MT versus delayed MT associated with BMT. There is thus an urgent need for randomized trials to define the effectiveness of MT in this patient subgroup. Abstract : Supplemental Digital Content is available in the text.